1997
DOI: 10.1177/096914139700400307
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Faecal Occult Blood Screening for Colorectal Cancer in a Well Defined French Population: Results of Five Screening Rounds from 1988 to 1996

Abstract: In France, a participation rate of over 50% can be achieved in colorectal cancer screening by means of a faecal occult blood test. To achieve this, primary care physicians have to play an active part in the programme and the test must be mailed to non-consultants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 14 publications
3
36
0
5
Order By: Relevance
“…It also represents the first such data internationally for a program that is based on VC. The adjusted overall participation rate in our program of 28.4% should be placed in context with Australian or French community-based screening programs of similar design using faecal occult blood testing (23-34% participation) 10,11 or flexible sigmoidoscopy (23%). 12 None of these studies had general practitioner involvement in recruitment and none had the publicity campaigns of mammography or cervical screening, which in Australia are accompanied by participation rates of 54% and 64% in the target age ranges 50-69 and 20-69 years respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It also represents the first such data internationally for a program that is based on VC. The adjusted overall participation rate in our program of 28.4% should be placed in context with Australian or French community-based screening programs of similar design using faecal occult blood testing (23-34% participation) 10,11 or flexible sigmoidoscopy (23%). 12 None of these studies had general practitioner involvement in recruitment and none had the publicity campaigns of mammography or cervical screening, which in Australia are accompanied by participation rates of 54% and 64% in the target age ranges 50-69 and 20-69 years respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the study has been reported previously (Tazi et al, 1997). Briefly, faecal occult blood screening using the Hemoccult II test was offered to all the residents of 12 well-defined administrative areas of Burgundy (France) who were born between 1914 and 1943.…”
Section: Study Settingmentioning
confidence: 99%
“…It is not known whether the results of these studies can be extrapolated to other countries (such as France) where the prognosis of CRC in the general population is better than in Denmark or England (Berrino et al, 1995). In this situation, the reduction in CRC mortality due to FOBT might be lower and a population-based controlled study of the question is under way in Burgundy (Tazi et al, 1997). The final results will be available within 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…The study design has been described previously (Tazi et al, 1997). All residents (n = 45 603) of 12 administrative districts of the department of Saône-et-Loire (Burgundy, France), born between 1914 and1943 (aged 45-74 years), were invited to participate in a mass screening programme for colorectal cancer.…”
Section: Methodsmentioning
confidence: 99%